Predicting Psychological Adaptation from Intercultural Sensitivity and Intergroup Contact through Intergroup Anxiety - Gebregergis, Werede Tareke; Csukonyi, Csilla (Journal of Ethnic and Cultural Studies, 2026)
Adapting to the social, cultural, and educational environment of a host society can be inherently taxing and stressful for student sojourners. Consequently, they are particularly vulnerable to a wide range of mental health complications, including depression, anxiety, psychological distress, low satisfaction, and low happiness. However, students with sufficient personal resources are believed to cope more effectively with these challenges. Considering the potential roles of these resources, the present study sought to examine the mediated effects of positive intergroup contact and intercultural sensitivity on psychological adaptation indices (i.e., depression-happiness continuum and life satisfaction) through intergroup anxiety. A total of 447 student sojourners were conveniently selected for the study, and they completed self-report questionnaires measuring intergroup contact, intercultural sensitivity, intergroup anxiety, depression-happiness, and life satisfaction. Pearson’s product-moment correlation, hierarchical multiple regression, and mediation analyses were conducted using SPSS v.26 and the jAMM module (medmod) jamovi software. The regression results indicated that positive intergroup contact and intercultural sensitivity significantly predicted both depression-happiness and life satisfaction. Mediation analyses further revealed that intergroup anxiety significantly mediated the relationships of both intergroup contact and intercultural sensitivity with the psychological indices of depression–happiness and life satisfaction. The results underline that positive intergroup contact and intercultural sensitivity can function as meaningful but modest psychosocial resources in facilitating psychological adaptation of student sojourners. Therefore, university communities should incorporate these aspects into their initiatives to address students’ mental health challenges.